Distant Companions Servants and Employers in Zambia, 1900-1985 - Hansen, Karen Tranberg (Cornell University Press, 1989)
Distant Companions tells the fascinating story of the lives and times of domestic servants and their employers in Zambia from the beginning of white settlement during the colonial period until after independence. Emphasizing the interactive nature of relationships of domination, the book is useful for readers who seek to understand the dynamics of domestic service in a variety of settings. In order to examine the servant- employer relationship within the context of larger political and economic processes, Karen Tranberg Hansen employs an unusual combination of methods, including analysis of historical documents, travelogues, memoirs, literature, and life histories, as well as anthropological fieldwork, survey research, and participant observation.